Increased Levels of Glycated Hemoglobin A1c and Iron Deficiency Anemia: A Review - Guo, Wenjia (Med Sci Monit, 2019)
Worldwide, the prevalence of diabetes remains high. Studies have shown that iron deficiency anemia (IDA) is associated with increased levels of glycated hemoglobin A1c (HbA1c), but the mechanism remains unclear. Hematological changes, iron metabolism, study methodology, and other factors could affect the results of diagnostic investigations, leading to false results. Red blood cell turnover in the bone marrow and the quality and heterogeneity of erythrocytes may influence the rate of hemoglobin glycation. By changing the structure of hemoglobin and inducing peroxidation, iron deficiency accelerates glycation. This review aims to discuss the possible causes of the association between increased levels of HbA1c and IDA.